2D and Quasi‐2D Halide Perovskites: Applications and Progress. Issue 2 (7th February 2020) - Kim, Hyojung; Huynh, Kim Anh; Kim, Soo Young; Le, Quyet Van; Jang, Ho Won
Abstract : 2D and quasi‐2D halide perovskites show a number of advantages for electronic and optoelectronic applications due to their tunable properties and superior stability. In article number 1900435, Quyet Van Le, Ho Won Jang and co‐workers review the atomic structures, optical properties, and electrical properties of 2D and quasi‐2D halide perovskites compared to their 3D counterparts. The authors summarize recent progress in applications using 2D and quasi‐2D halide perovskites, such as solar cells, light emitting diodes, photodetectors, resistive random access memories, and artificial synapses. Main parameters that regulate the device performance are addressed, as well as strategies for improving materials properties and device performance for each application.